The Great Kiwi (Dis)Connect: The New Provinces Act and its Consequences - Brett, Andre (2012)
In 1853, New Zealand began a quasi-federal experiment that ended surprisingly quickly. New Zealand's Pakeha (white) settlers, many influenced by the Chartist movement, had migrated in the expectation that they would possess the same rights as Englishmen at home. After vociferous agitation and a false start when an earlier constitution was blocked as unworkable, they were granted a representative constitution that contained a system of six provinces.2 Five of the provinces quickly established ministries that were wholly or partially responsible to the legislature, and responsible government at the national level followed in 1856. 3 Although responsible government followed similar lines to that in the Australian colonies, governors retained the power to veto financial bills and Australia had no equivalent to New Zealand's provincial system or its superintendents, some of whom viewed the superintendency as akin to a lieutenant-governorship.